Występowanie ozorka dębowego Fistulina hepatica (Schaeff.): Fr. oraz związanego z nim gatunku chrząszcza Triphyllus bicolor (Fabr.) w rezerwacie „Las Natoliński” - Piętka, Jacek; Borowski, Jerzy (Leśne Prace Badawcze, 2011)
The study presents data on the occurrence of fungus Fistulina hepatica and beetle Triphyllus bicolor in the Warsaw Natolin Forest Reserve. During the inspection carried out in 2005-2007, the fruiting bodies of F. hepatica were found on 83 oak trees. The stem circumference of each tree with fruiting bodies was measured and the number of fruiting bodies, and their position on the tree trunk (height, geographical direction), were recorded. In the spring of 2009, tar traps with sawdust substrate overgrown by F. hepatica mycelium were hung in places where its fruiting bodies had previously been observed. A total of 32 individuals of the beetle T. bicolor were caught in these traps during July and August.